Historical Changes in Wind‐Driven Ocean Circulation Can Accelerate Global Warming. Issue 4 (22nd February 2023) - McMonigal, Kay; Larson, Sarah; Hu, Shineng; Kramer, Ryan
Abstract: Mitigation and adaptation strategies for climate change depend on accurate climate projections for the coming decades. While changes in radiative heat fluxes are known to contribute to surface warming, changes to ocean circulation can also impact the rate of surface warming. Previous studies suggest that projected changes to ocean circulation reduce the rate of global warming. However, these studies consider large greenhouse gas forcing scenarios, which induce a significant buoyancy‐driven decline of the Atlantic Meridional Overturning Circulation. Here, we use a climate model to quantify the previously unknown impact of changes to wind‐driven ocean circulation on global surface warming. Wind‐driven ocean circulation changes amplify the externally forced warming rate by 17% from 1979 to 2014. Accurately simulating changes to the atmospheric circulation is key to improving near‐term climate projections. Plain Language Summary: Global warming of surface air temperature is largely due to increases in greenhouse gases, which lead to increased radiative heat fluxes toward Earth's surface. However, the exact pattern and rate of global warming are also influenced by the uptake and redistribution of heat by the ocean, which can be altered by warming. Previous studies have quantified the role of the changing ocean circulation as a whole on the rate and pattern of global warming. However, the relative contribution of different ocean dynamical processes has not been explored yet. Ocean circulation can broadly be divided into components driven by wind and density differences. Here, we quantify the role of changes to the wind‐driven ocean circulation onto global air temperature warming. We find that changes to the wind‐driven ocean circulation amplify global warming by 17% from 1979 to 2014. Climate models need to adequately simulate changes to the winds, and the ocean's response to these wind changes, to accurately project climate change. Key Points: Externally forced changes to wind‐driven ocean circulation accelerate global warming by 17% in a coupled climate model The Antarctic Circumpolar Current and Pacific Ocean circulations are influenced by externally forced wind stress changes Externally forced changes to wind‐driven ocean circulation amplify Southern Hemisphere warming